Effectiveness of Authentic Assessment in EFL Classes - Nazer Hashemi, Nadia (Journal of Social Sciences - Kabul University, 2021)
This study examines the impact of authentic and traditional assessment methods on improving EFL learners' performance. The term "authentic assessment" refers to various forms of assessment that reflect student learning, achievement, motivation, and attitudes through instructionally relevant classroom activities. Assessment plays a crucial role in learning and teaching in higher education, serving as both a learning tool and a means to determine students' success. In the past, many language teachers were unaware of the importance of authentic assessment in the learning process. However, in recent years, greater attention has been given to its significance. According to Biggs (2003), assessment is essential for tracking learners' progress, ensuring accountability, and achieving accreditation.